Relevance of Science Education for Self-reliance and National Economic Development - Tijani, Bamidele Emmanuel; Adeduyigbe, Adeniyi Michael (SEAMEO QITEP in Science, 2025)
This study investigates the role of science education as a catalyst for economic development and self‐reliance by drawing on case studies from developed countries and synthesising key themes from a systematic literature review. Using qualitative content analysis of 15 selected studies, the review reveals that integrating rigorous theoretical instruction with practical, hands-on training, as exemplified by Germany’s dual education system, South Korea’s integrated science and technology approach, the innovation-driven environment in the United States, and Israel’s agri-tech successes, can enhance workforce readiness, drive technological innovation, and stimulate entrepreneurial activity. These international examples provide valuable insights for Nigeria, suggesting that similar strategies could improve local economic competitiveness and reduce dependency on foreign expertise. However, the study also identifies significant challenges, including inadequate funding, outdated curricula, and insufficient infrastructural support, which hinder the full realisation of science education’s potential. The findings underscore the need for targeted educational reforms and strategic investments to translate these benefits into sustainable economic growth and development.